A man with hereditary exostoses and high-grade non-Hodgkin's lymphoma of the bone - Neben, Kai; Werner, M.; Bernd, Ludger; Ewerbeck, Volker; Delling, G.; Ho, Anthony Dick (Annals of hematology, 2001)
Multiple cartilaginous exostoses (MCE) is an autosomal dominant disorder that can lead to malignant transformation from exostoses to a secondary chondrosarcoma. We present a case report of a 52-year-old man with MCE who had a palpable mass at the left shoulder. At the site of the left proximal humerus, a cartilaginous exostosis was localized, suggesting that the tumor developed by a malignant transformation of an exostosis into a secondary chondrosarcoma. Interestingly, a biopsy showed a diffuse large B-cell lymphoma with Burkitt-like features. To our knowledge, the association of high-grade lymphoma and hereditary exostoses has not been described previously. This case demonstrates that a malignant tumor at the location of a cartilaginous exostosis is not necessarily a chondrosarcoma and that a biopsy is an essential part of the diagnostic work-up.
Gesehen am 21.12.2021